2023
DOI: 10.3390/ph16081182
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin Alleviated Inflammasome-Mediated Pyroptosis and Modulated the mTOR/P70S6/P6/eIF4E/4EBP1 Pathway in Ischemic Stroke

Abdullah Alattar,
Reem Alshaman,
Yusuf S. Althobaiti
et al.

Abstract: Stroke ranks as the world’s second most prevalent cause of mortality, and it represents a major public health concern with profound economic and social implications. In the present study, we elucidated the neuroprotective role of quercetin on NLRP3-associated pyroptosis, Nrf2-coupled anti-inflammatory, and mTOR-dependent downstream pathways. Male Sprague Dawley rats were subjected to 72 h of transient middle cerebral artery ischemia, followed by the administration of 10 mg/kg of quercetin. Our findings demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Evidence indicates cross-talks between NFκB and Nrf2, a transcription protein that activates the endogenous inducible antioxidant proteins such as HO-1 [ 66 , 67 ]. Our study demonstrated elevated expressions of inflammatory mediators and pro-inflammatory cytokines along with cytoprotective Nrf2 and HO-1 in the ischemic brain while quercetin modulated these changes which is consistent with previous findings that suggest a strong anti-inflammatory potential of quercetin in various models of ischemic stroke [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Evidence indicates cross-talks between NFκB and Nrf2, a transcription protein that activates the endogenous inducible antioxidant proteins such as HO-1 [ 66 , 67 ]. Our study demonstrated elevated expressions of inflammatory mediators and pro-inflammatory cytokines along with cytoprotective Nrf2 and HO-1 in the ischemic brain while quercetin modulated these changes which is consistent with previous findings that suggest a strong anti-inflammatory potential of quercetin in various models of ischemic stroke [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 92%
“…We did not employ randomization or blind allotment of rats; nevertheless, we followed the criterion of keeping animals of comparable weight in the same cohort under the same test conditions. Each of the four groups of rats was randomly assigned to receive quercetin therapy or sham surgery (n = 13/group), MCAO (middle cerebral artery occlusion), Qur + MCAO (quercetin treatment in conjunction with middle cerebral artery occlusion), sham and Qur + sham [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a protective effect on neurodegenerative diseases and can signi cantly improve learning, memory, and cognitive impairmen (Paula et al, 2019). According to literature reports, Que can regulate autophagy through the DK/AKT/mTOR pathway to alleviate neurological damage caused by stroke (Alattar et al, 2023). There are also studies indicating that Quercetin can prevents COV-induced hippocampal damage by enhancing the antioxidant system and preventing cell apoptosis (Sadeghi et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols comprise a diverse group of antioxidants, sharing a common feature of containing at least one aromatic ring with multiple hydroxyl groups [ 54 ]. Some polyphenols, such as resveratrol [ 68 ], curcumin [ 69 ], and quercetin [ 70 ], have been studied to assess their neuroprotective effects, and several mechanisms have been implicated.…”
Section: Antioxidant Bioactive Molecules Against Ischemic Strokementioning
confidence: 99%